Constraints on the formation and properties of a Martian lobate debris apron: Insights from high‐resolution topography, SHARAD radar data, and a numerical ice flow model. Issue 3 (30th March 2016) - Parsons, Reid; Holt, John
Abstract: Lobate debris aprons (LDAs) are midlatitude deposits of debris‐covered ice formed during one or more periods of glaciation during the Amazonian period. However, little is known about the climate conditions that led to LDA formation. We explore a hypothesis in which a single, extended period of precipitation of ice on the steep slopes of Euripus Mons (45°S, 105°E—east of the Hellas Basin) produced a flowing ice deposit which was protected from subsequent ablation to produce the LDA found at this location. We test this hypothesis with a numerical ice flow model using an ice rheology based on low‐temperature ice deformation experiments. The model simulates ice accumulation and flow for the northern and southern lobes of the Euripus Mons LDA using basal topography constrained by data from the Shallow Radar (SHARAD) and a range of ice viscosities (determined by ice temperature and ice grain size). Simulations for the northern lobe of the Euripus LDA produce good fits to the surface topography. Assuming an LDA age of ∼60 Myr and an expected temperature range of 200 to 204 K (for various obliquities) gives an ice grain size of ≈2 mm. Simulations of the southern section produce poor fits to surface topography and result in much faster flow timescales unless multiple ice deposition events or higher ice viscosities are considered. Key Points: N and S section of LDA contrast in their age, accumulation history, or ice viscosity The temperature of the ice is not likely to differ by < few Kelvin, and age is likely similar Shape of the topographic profiles may indicate multiple deposition events